Periodisasi Sejarah Sastra Masa Andalusia: (Kajian Historis) - Nisa', Ida Chairun; Budi, Rahmat Dinni Haerul (Universitas Islam Negeri Alauddin Makassar, 2024)
The periodization of Arabic literature in Andalusia as shown by historians differs from one another. This is interesting to research, especially examining the differences in periodization. This research aims to find a reliable chronology of the periodization of the history of Arabic literature in Andalusia. To find the correct chronology of the periodization of Arabic literary history, researchers use historical methods. Researchers found the following periodization: chronologically, the historical periods of Arabic literature in Andalusia are divided into six. First, 711-755 AD, no literary manuscripts have been found. Second, 755-912 AD, literary texts were found under Ad-Dakhil's reign but were still oriented towards Masyriq literature. Third, 912-1013 AD, namely the period when the group of kings called